1998
DOI: 10.1111/j.1438-8677.1998.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Colonisation and Celibacy: Population Structure in Central European Trichomanes speciosum (Pteridophyta)

Abstract: The Killarney fern Trichomanes speciosum Willd. (Hymenophyllaceae) is unique in possessing both extensive sexual (sporophyte and gametophyte generations present) and asexual (gametophyte only) ranges. It was first discovered in central Europe in 1993 and is represented in this area only by its perennial, vegetatively propagating gametophyte generation. Genetic variation has been investigated at 35 sites. Allozyme diversity is partitioned primarily between, not within, sites. Although genetic variation exists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…Moreover, future studies using these 10 microsatellite markers will allow questions about the biogeographic history of V. speciosa to be tested, such as the refugial status of its populations. Our results in this study show two sporophyte populations in the Iberian Peninsula—considered a glacial refuge (Bennett et al, 1991)—to be moderately diverse (AZK in the north being more diverse than COQ in the south), which contrasts with the lack of genetic diversity detected within Northern and Central European populations using allozyme markers (Rumsey et al, 1998b, 1999, 2005). …”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Moreover, future studies using these 10 microsatellite markers will allow questions about the biogeographic history of V. speciosa to be tested, such as the refugial status of its populations. Our results in this study show two sporophyte populations in the Iberian Peninsula—considered a glacial refuge (Bennett et al, 1991)—to be moderately diverse (AZK in the north being more diverse than COQ in the south), which contrasts with the lack of genetic diversity detected within Northern and Central European populations using allozyme markers (Rumsey et al, 1998b, 1999, 2005). …”
Section: Discussioncontrasting
confidence: 67%
“…Earlier studies on the population genetics of V. speciosa have used allozymes as molecular markers and, although with low resolution, they have contributed to an understanding of the current distribution of V. speciosa (Rumsey et al, 1996(Rumsey et al, , 1998b(Rumsey et al, , 1999(Rumsey et al, , 2005. Because V. speciosa is a tetraploid species (Manton, 1950;Manton et al, 1986), the allozyme banding patterns were coded as phenotypes in all the cited studies, thus decreasing further the resolution capacity of the allozymes.…”
Section: Applications In Plant Sciencesmentioning
confidence: 99%
“…At some localities the two taxa grow very closely together on the same outcrop. Rumsey et al . (1998a ) investigated the genetic diversity in isolated gametophyte colonies of T. speciosum from the same area in western Germany.…”
Section: Discussionmentioning
confidence: 99%
“…However, these gemmae are unlikely to survive long‐range transport because of irreversible desiccation ( Rumsey & Sheffield, 1996). A local clustering of genetic variation was observed in T. speciosum gametophyte populations from the same area and genetic variability was partitioned mainly between populations ( Rumsey et al ., 1998a ).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomanes speciosum represents an obvious Tertiary relict. However, it is suggested that the colonies of gametophytes in central Europe arose through colonization by long-distance dispersal from refugia in Macaronesia during the Atlantic period (Rumsey et al 1998b). Gametophytes in central Europe inhabit crevices and small caves in acidic sandstone rocks.…”
Section: Rubusmentioning
confidence: 99%